Fostering environmental and resources management in Sudan through geo-information systems: A prospective approach for sustainability - Osman, Mohamed B.O.; Yassin, Emad E.H. (Journal of Degraded and Mining Lands Management, 2024)
Environmental and land resource degradation is a serious problem that poses significant challenges in Sudan and worldwide generally. Despite the fact that the physical environment components are the underlying economic resources and production assets in developing countries like Sudan, and they directly affect the nation’s socioeconomic aspects of income, health, water availability, food security, and many others. The interventions and protective measures were insufficient to meet the magnitude and extent of the ongoing degradation and resource wastage. Based on the analysis of the indicators and trends of the environmental and natural resources management ‘status quo’, this paper is an attempt to overview and investigate the state of environmental and natural resources management and governance in Sudan. Further discussion delves into the utilization of geo-information systems in Sudan’s environmental and resource management by analyzing and reviewing “some previous case studies” where GIS approaches and techniques were deployed. The paper further strives to explore and highlight the opportunities and potential contributions of GIS in the context of Sudan’s environmental and resource management. Lessons learned from the previous experiences were considered, and the recommendations for the future use of a tailored geo-information system in Sudan context were highlighted and suggested to support better practices and sustainability insights for environmental governance and resources management.